A New Ornithidium (Orchidaceae: Maxillariinae) from the Massif de la Hotte of Haiti - Ackerman, James D. (Universidad de Costa Rica, 2013)
A new species of Ornithidium from the Massif de la Hotte, one of the last remaining orchid-rich regions of Haiti, is described and illustrated. Collected in the 1980s by Donald D. Dod whose original specimen has been lost and whose live plants only just recently flowered, the new species is closely related to O. coccineum based on both morphology and molecular sequences. It is distinguished from the latter by shorter apical leaves, globose pseudobulbs and longer sepals.